First manic episode in 14-year-old adolescent during COVID-19 pandemic lockdown measures: A case report - Simone Marchini; Ode Van Ormelingen; Marie Delhaye (Annals of Psychiatry and Treatment - Peertechz Publications, 2020)
The authors describe a 14-year-old adolescent presenting a first manic episode begun during COVID-19 lockdown measures. The patient was experiencing extreme psychological discomfort about the lockdown measures. Family environment was described as stressful and freedom limitation perceived as extremely oppressive. The inpatient care and pharmacological intervention allowed rapid symptoms remission. The present early onset manic episode follows the model combining the personal vulnerability with a strong triggering factor. The authors conclude that the role of COVID-19 pandemic and its implication on adolescent's mental health needs to be further investigated.